The Effectiveness of Using Creative Recycled Savings in Improving Financial Literacy of Early Childhood - Nur Alifah; Muh Rifki; Nurhana Eka Maharani; Nurul Asmaul Husna; Miftahul Jannah; Ahmad Faudzan; Muhammad Ilham; Amalia Mangit (Journal of Community Service: In Economics, Bussiness, and Islamic Finance, 2026)
Early childhood financial literacy education is important for developing thrifty behavior. However, students at Biro state elementary school are still consumptive and lack understanding of the concept of saving. This community service aims to improve financial literacy through the creation of recycled savings from used bottles. The method used is Participatory Learning, including socialization, piggy bank-making training, and evaluation. Results show a significant increase in students’ understanding from 35% (pre-test) to 90% (post-test). This program is effective in building disciplined character and environmental awareness, as well as providing alternative creative learning media for schools.